2009
DOI: 10.1186/1475-2875-8-228
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles mortality is both age- and Plasmodium-density dependent: implications for malaria transmission

Abstract: BackgroundDaily mortality is an important determinant of a vector's ability to transmit pathogens. Original simplifying assumptions in malaria transmission models presume vector mortality is independent of age, infection status and parasite load. Previous studies illustrate conflicting evidence as to the importance of Plasmodium-induced vector mortality, but very few studies to date have considered the effect of infection density on mosquito survival.MethodsA series of three experiments were conducted, each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 85 publications
5
121
2
Order By: Relevance
“…Evidence is now accumulating that input parasite densities affect the progression of the infection as well as mosquito signaling pathways and mortality; however, the actual impact of infection intensities on mosquito responses is still unclear, and very few studies have considered infection intensities in the analysis of infection data (7,24,26). Here we have carried out A. gambiae infections with geographically related P. falciparum parasites sampled from naturally infected children in order to investigate the impact of different infection intensities on the mosquito midgut transcriptome.…”
Section: Rna Interference (Rnai)-mediated Gene Silencing Provides Inimentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is now accumulating that input parasite densities affect the progression of the infection as well as mosquito signaling pathways and mortality; however, the actual impact of infection intensities on mosquito responses is still unclear, and very few studies have considered infection intensities in the analysis of infection data (7,24,26). Here we have carried out A. gambiae infections with geographically related P. falciparum parasites sampled from naturally infected children in order to investigate the impact of different infection intensities on the mosquito midgut transcriptome.…”
Section: Rna Interference (Rnai)-mediated Gene Silencing Provides Inimentioning
confidence: 99%
“…In fact, A. gambiae is not a natural vector of P. berghei, and the intensities of P. berghei infection are much higher than those commonly observed in nature with P. falciparum (2). Differences in P. falciparum infection levels have been associated with several genomic loci and have been shown to depend on vector-parasite genotype-by-genotype interactions (12,16,29).Evidence is now accumulating that input parasite densities affect the progression of the infection as well as mosquito signaling pathways and mortality; however, the actual impact of infection intensities on mosquito responses is still unclear, and very few studies have considered infection intensities in the analysis of infection data (7,24,26). Here we have carried out A. gambiae infections with geographically related P. falciparum parasites sampled from naturally infected children in order to investigate the impact of different infection intensities on the mosquito midgut transcriptome.…”
mentioning
confidence: 99%
“…[8][9][10] These concerns would be minor if vectorial capacity in two environments were to be overestimated or underestimated to the same degree (i.e., a quantitative difference), 5 but they could be particularly serious if use of an exponential mortality function results in qualitatively different outcomes when environments or success of control measures are compared. One theoretical investigation so far suggests that this may be the case.…”
Section: Introductionmentioning
confidence: 99%
“…Dawes et al also reported age-dependent mortality in laboratory adult populations of An. stephensi [2]. Mosquito senescence has been documented in Aedes aegypti, both under laboratory and semi-field conditions [36,37].…”
Section: Discussionmentioning
confidence: 99%